Developing Targeted Health Service Interventions Using the PRECEDE-PROCEED Model: Two Australian Case Studies - Jane L. Phillips; John X. Rolley; Patricia M. Davidson (Hindawi Limited, 2012)
Aims and Objectives. This paper provides an overview of the applicability of the PRECEDE-PROCEED Model to the development of targeted nursing led chronic illness interventions. Background. Changing health care practice is a complex and dynamic process that requires consideration of social, political, economic, and organisational factors. An understanding of the characteristics of the target population, health professionals, and organizations plus identification of the determinants for change are also required. Synthesizing this data to guide the development of an effective intervention is a challenging process. The PRECEDE-PROCEED Model has been used in global health care settings to guide the identification, planning, implementation, and evaluation of various health improvement initiatives. Design. Using a reflective case study approach, this paper examines the applicability of the PRECEDE-PROCEED Model to the development of targeted chronic care improvement interventions for two distinct Australian populations: a rapidly expanding and aging rural population with unmet palliative care needs and a disadvantaged urban community at higher risk of cardiovascular disease. Results. The PRECEDE-PROCEED Model approach demonstrated utility across diverse health settings in a systematic planning process. In environments characterized by increasing health care needs, limited resources, and growing community expectations, adopting planning tools such as PRECEDE-PROCEED Model at a local level can facilitate the development of the most effective interventions. Relevance to Clinical Practice. The PRECEDE-PROCEED Model is a strong theoretical model that guides the development of realistic nursing led interventions with the best chance of being successful in existing health care environments.